Guide to international environmental law - Kiss, Alexandre Charles, 1925-2007 (Martinus Nijhoff Publishers, 2007)
Aims to present the essential elements of international environmental law. This book provides a general overview of why and how the international system elaborates environmental obligations and monitors compliance with them.